Postfeminism and Contemporary Hollywood Cinema - Gwynne, J.; Muller, N.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
By analyzing the negotiation of femininities and masculinities within contemporary Hollywood cinema, Postfeminism and Contemporary Hollywood Cinema presents diverse interrogations of popular cinema and illustrates the need for a renewed scholarly focus on contemporary film production.
Keywords: Motion pictures—United States; Motion pictures—History.; Arts; Motion pictures and television; Film genres; Communication; American Cinema and TV; Film History; Arts; Screen Studies; Genre; Media Studies